2014
DOI: 10.1001/jamaneurol.2013.4749
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcome of Fetal Cell Transplantation for Parkinson Disease

Abstract: IMPORTANCE Recent advances in stem cell technologies have rekindled an interest in the use of cell replacement strategies for patients with Parkinson disease. This study reports the very long-term clinical outcomes of fetal cell transplantation in 2 patients with Parkinson disease. Such long-term follow-up data can usefully inform on the potential efficacy of this approach, as well as the design of trials for its further evaluation. OBSERVATIONS Two patients received intrastriatal grafts of human fetal ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
231
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 276 publications
(244 citation statements)
references
References 21 publications
(36 reference statements)
4
231
0
1
Order By: Relevance
“…It has been found that transplantation of the abovementioned tissue can improve movement related problems in PD patients [38]. In a relevant study, it was found that the motor symptoms can improve even for eighteen years after transplantation [39,40]. In addition, some studies exist which showed contradictory results which oppose the above findings [41,42].…”
Section: Mesencephalic Tissue Of the Human Fetusmentioning
confidence: 98%
“…It has been found that transplantation of the abovementioned tissue can improve movement related problems in PD patients [38]. In a relevant study, it was found that the motor symptoms can improve even for eighteen years after transplantation [39,40]. In addition, some studies exist which showed contradictory results which oppose the above findings [41,42].…”
Section: Mesencephalic Tissue Of the Human Fetusmentioning
confidence: 98%
“…Overall the findings from this study provide the first human evidence for the role of striatal serotonergic ternimals in LIDs pathophysiology and support the development of selective 5-HT 1A agonists for use as antidyskinetic agents in PD. Serotonin terminals are also involved in graft-induced dyskinesias (GIDs), which are involuntary movements when "off" dopaminergic drugs occurring after transplantation of fVM tissue (Kefalopoulou et al, 2014;Politis, Loane, et al, 2011;Politis, Oertel, et al, 2011;Politis, Wu, Loane, Kiferle, et al, 2010;Politis, Wu, Loane, Quinn, et al, 2010;Politis, Wu, Loane, Turkheimer, et al, 2010 PET studies have shown that three PD patients who received striatal transplantation with fVM tissue and exhibited GIDs had excessive graft-derived serotonergic innervation and high serotonin-to-dopamine terminal ratio (Politis, Loane, et al, 2011;Politis, Oertel, et al, 2011;Politis, Wu, Loane, Kiferle, et al, 2010;Politis, Wu, Loane, Quinn, et al, 2010;Politis, Wu, Loane, Turkheimer, et al, 2010). Administration of small, repeated doses of buspirone, was able to attenuate GIDs possibly by attenuating the abnormal serotonin terminal-derived dopamine release (Loane & Politis, 2012;Politis, 2010Politis, , 2011Politis, Loane, et al, 2011;Politis, Oertel, et al, 2011;Politis, Wu, Loane, Kiferle, et al, 2010;Politis, Wu, Loane, Quinn, et al, 2010;Politis, Wu, Loane, Turkheimer, et al, 2010).…”
Section: Serotonergic Systemmentioning
confidence: 99%
“…First clinical trials (Lindvall et al, 1988) were again initially promising (Lindvall et al, 1990) but were later held back due to efficiency concerns following studies with a larger number of patients and randomized, double-blind, placebo-controlled protocols (Freed et al, 2001;Olanow et al, 2003) that showed no significant difference between grafted patients and placebo, with several patients developing graft-induced dyskinesia. Nevertheless, retrospective analyses and reports on those clinical trials of fVM striatal grafts demonstrated their efficiency either clinically (Kefalopoulou et al, 2014), histologically (Li et al, 2016), behaviorally (Gordon et al, 2004) or functionally (Politis and Piccini, 2010). Based on all these evidences, a new clinical trial of fVM transplantation has been started on a cohort of patients with improved grafting procedures and selection of patients (Moore et al, 2014) with the aim of preparing for the move to stem-cell-based transplantation in humans while waiting for preclinical investigation reports in animal models.…”
Section: Fetal Ventral Mesencephalonmentioning
confidence: 99%